L'entretien des sols à olivier en milieu aride : conséquences agronomiques et maîtrise par l'agriculteur - Ben Rouina B.; Yousfi M.; M'Laouah M.; Louizi A. (Agriculture, durabilité et environnement, 1995)
Orchard tillage was considered fundamental in order to increase growth and yield of olive trees, especially in arid zones where rainfall varies considerably, and it is not well spread over time and does not exceed 250-300 mm per year. However, instead of the traditional tillage practices which had proved their efficiency, the using of anarchic motorization during the two last decades had generated a degradation, then a destruction of the soil structure and soil erosion, particularly in those fragile ecosystems. In order to assess the tilling system impact and their influence, both on the soil agronomical properties and the olive-tree growth and production, the effect of tilling tools was studied in field experiments. The preliminary results show that: (i) a lack of rainfall water has a negative impact on growth and reproduction development in cultivated dry areas; (ii) the tillage practices permit a control of weed development and to favour the multiplication of the infiltration preferential paths; (iii) the water infiltration and retention, the water behaviour and the root growth improved when the soil was ploughed in winter (20-25 cm deep).
Séminaire de l'Association Tunisienne des Anciens de l'Institut Agronomique Méditerranéen de Zaragoza (ATA-IAMZ), 1993/12/02-03, Tunis (Tunisia)